The value of genetic resources in agriculture: a meta-analysis assessing existing knowledge and future research needs - Ahtiainen, Heini; Pouta, Eija (Taylor & Francis, 2011)
The protection of genetic resources in agriculture is an important aspect of biodiversity conservation. Knowledge of the value of genetic resources can contribute to determining the appropriate focus and extent of conservation. This study reviewed and summarised literature on the economic value of genetic resources using meta-analysis. Altogether, 22 studies were used to describe current knowledge on the value of genetic resources. Furthermore, 14 studies with 93 value observations were examined with a meta-regression model to identify variables that explain the willingness-to-pay (WTP) for or willingness-to-accept (WTA) loss of genetic resources. Grain genetic resources were ascribed lower value compared to animal genetic resources (AnGR) and agrobiodiversity, and the values of breeds or varieties and conservation programmes were higher than the value of individual attributes. Future research should address the gaps in knowledge that are relevant for policy-making. This particularly includes improving knowledge on the value of plant genetic resources (PGR), obtaining value estimates for maintaining genetic diversity in Europe and the United States, estimating the relative magnitude of use and non-use values and determining the value consumers place on genetic resources and diversity in agriculture. An extensive database with valuation literature on genetic resources that fulfils the requirements for benefit transfer is essential to utilise value information more efficiently in decision-making situations.
Keywords: Ma; geenivarat; suojelu; arvostus; agriculture; genetic resources conservation; valuation; meta-analysis; willingness-to-pay